Pengaruh Pemberian POC Urine Sapi Terhadap Pertumbuhan dan Hasil Kubis Bunga (Brassica oleracea var. Bottrytis L.) pada Tanah Inceptisol : The effect of giving poc cow urine on the growth and results of flowering cabbage plant (brassica oleracea var. Botrytis l.) In inceptisol soil - Abdul Hamid, Syahrudin; Darung , Untung; Cesarianto , Andreyan; Abdul Syahid , Abdul Syahid; Vetrani Asie , Kambang; `Oemar, Oesin; Apung Atikah, Titin (AgriPeat, 2024)
The aim of the research was to determine the effect of applying cow urine liquid organic fertilizer on the growth and yield of flowering cabbage plants (Brassica oleracea var. Botrytis L.) on inceptisol soil. The research was carried out in March 2023 – August 2023 in Palangka Raya City, Central Kalimantan Province.  The research used a Randomized Group Design (RAK) with 6 treatment levels of cow urine POC doses, namely: 0; 15; 30; 45; 60; and 75 ml L-1 water.  The results showed that administration of various doses of POC cow urine had a significant effect on the growth and yield of flowering cabbage in inceptisol soil. Giving cow urine POC at a dose of 75 ml L-1 of water is the best treatment for the growth and yield of flowering cabbage with an average crop weight of 379 g or 16 tons/ha